Indeks Massa Tubuh sebagai Biomarker Prognostik untuk Akne Vulgaris: Suatu Tinjauan Sistematis tentang Pencegahan dan Terapi - Ni Made Suari Asih; Ida Ayu Diah Purnama Sari; Bayu Kresna Wiratama (Jurnal Kesehatan Mahardika, 2025)
Acne vulgaris is one of the most common dermatological conditions affecting more than 0.5 billion people worldwide. Several studies have shown that body mass index has a positive correlation with acne vulgaris. This systematic review aims to evaluate whether body mass index can serve as a prognosic biomarker for the severity of acne vulgaris due to prevention and therapeutics of acne vulgaris. A systematic search was conducted using Publish or Perish following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). Studies included human participants aged 14–22 from Asia. Nine studies met the inclusion criteria, encompassing 1,563 participants (including acne cases and controls where applicable). Five studies demonstrated a statistically significant correlation between body mass index and acne severity. The remaining four showed inconsistent or non-significant associations, potentially due to differences in sample size, population characteristics, or control for confounding factors such as diet, hormonal status, and medication use. Most studies used standardized acne severity scales such as the Global Acne Grading System (GAGS). The findings indicate that high body mass index are generally associated with increased severity of acne vulgaris, supporting the potential body mass index could be a valuable addition to acne prevention and management strategies.